2018
DOI: 10.1051/matecconf/201823903002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of opposite elevation on the occupancy level of the tracks of sorting park

Abstract: The purpose of this paper is to study the effect of the location and magnitude of opposite elevation on the occupancy level of the tracks of sorting park. The subject of the study is the effect of the magnitude and location of opposite elevation on the sorting tracks occupancy level. The object is the tracks of sorting park. For the study, a simulation model of the traffic of the cut in sorting park was used, taking into account the reverse movement, “SortPark”. On the basis of this model, it was concluded tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The objective of the "Rehabilitation of the Volga" project is to reduce the volume of wastewater discharged into the Volga by three times from 3.2 km3 to 1.1 km3. In addition, it is planned to begin the restoration of the banks, as well as to raise 95 vessels from the bottom, which harm the water area of the river [4][5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…The objective of the "Rehabilitation of the Volga" project is to reduce the volume of wastewater discharged into the Volga by three times from 3.2 km3 to 1.1 km3. In addition, it is planned to begin the restoration of the banks, as well as to raise 95 vessels from the bottom, which harm the water area of the river [4][5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…The asphalt concrete physical-mechanical and designed characteristics were determined according to functional regulations [12,14,15].…”
Section: Asphalt Concrete Testing Proceduresmentioning
confidence: 99%
“…For different damping values, there will be different forms of response spectra. [14,15] To take into account the damping properties of various building materials, it is necessary to build a family of spectral curves with different damping coefficients . In this case , laboratory tests were performed where the damping value was determined.…”
Section: Analysis Of the Response Spectrummentioning
confidence: 99%
“…Since the velocity spectrum thus obtained is not accurate, it is called the pseudospectrum. [11,14] It can be shown that to construct the spectra, it is sufficient to determine only the spectrum of pseudo-velocities using the formula:…”
Section: Analysis Of the Response Spectrummentioning
confidence: 99%
See 1 more Smart Citation